ONLINE TRAINING FOR THE LABOUR FORCE: A BIBLIOMETRIC ANALYSIS OF CURRENT TRENDS - Rahayu Ahmad-Don; Ahmad Suffian Mohd Zahari; Zalinawati Abdullah (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
The increasing integration of online training into the labour force has transformed traditional workforce development strategies, offering flexible and scalable solutions to skill enhancement. However, the rapid proliferation of research in this field necessitates a comprehensive analysis to discern patterns, trends, and gaps. This study presents a bibliometric analysis of online training in the labour force, utilising data sourced from the Scopus database. A total of 1,042 records were retrieved and analysed using Scopus Analyzer and VOSviewer software. The analysis aimed to uncover publication trends, prominent authors, key journals, influential institutions, and core thematic areas. Methodologically, the study adhered to bibliometric protocols, employing citation mapping, co-authorship networks, and thematic clustering. Key findings revealed an exponential publication growth over recent years, with significant contributions from North America and Europe. VOSviewer analysis highlighted major thematic areas such as e-learning technologies, workforce productivity, and the role of digital tools in skill development. The study also identified a concentration of research in a limited number of high-impact journals, underscoring the dominance of established platforms in disseminating knowledge. Despite these advancements, the findings highlight gaps in empirical studies focusing on developing regions and sector-specific applications. This bibliometric analysis contributes to understanding the evolving landscape of online training in the labour force, providing valuable insights for researchers, policymakers, and practitioners aiming to address existing challenges and leverage future opportunities in this dynamic domain.